Association between deployment and Gulf War Illness and adverse COVID outcomes in a nationwide cohort of 1990–1991 Gulf Era war veterans in the VA’s Million Veteran Program - Donna L. White; Alice B. S. NonoDjotsa; Sarah T. Ahmed; Stephen H. Boyle; J. Michael Gaziano; Andrew D. Thompson; Melissa G. Johnson; Elizabeth J. Gifford; Renato Polimanti; Mihaela Aslan; Elizabeth R. Hauser; Drew A. Helmer (PLoS ONE, 2026)
Background U.S. military veterans deployed to the Persian Gulf to serve in the 1990–1991 Gulf War (GWVs) have expressed concerns about potential increased risk of experiencing adverse COVID-related health outcomes given broad near-unique exposure to multiple diverse toxic agents during deployment and ongoing ~30% prevalence of Gulf War Illness (GWI+), a chronic, medically unexplained multi-symptom disorder associated with inflammation and immune dysregulation. Methods We conducted a retrospective study in the largest nationwide research cohort of 1990−1991Gulf War era veterans (GWEVs) enrolled in the VA’s nationwide Million Veteran Program (MVP) to interrogate: 1) if deployed GWVs had increased risk for testing positive for novel SARS-CoV-2 infection (COVID+), COVID-related hospitalization, ICU admission, or death in 2020 (pre-vaccine period); and 2) if deployed GWVs with GWI + had particularly increased susceptibility. COVID outcomes ascertained using VA’s COVID Data Resource; GWI + determined using CDC severe criteria in surveyed GWV subcohort. Findings Our overall GWEV cohort (N = 136,868) had mean age 60.7 years, with 84% male, 27% African-American, and 22% deployed; n = 26,141 COVID-tested in 2020. COVID test-positivity (COVID + ) was slightly higher in deployed GWVs (18.8% vs. 17.2% in non-deployed GWEVs, p = 0.005). In multivariable logistic models, there were neither strong nor significant associations between deployment and testing COVID + , COVID-related hospitalization or ICU admission (adjusted [adj] ORs ranged from 0.90–1.06, all p-values >0.05), nor significant differences in COVID-related mortality. Preliminary analysis in our pre-pandemic surveyed deployed GWV subcohort (N = 1,643 COVID-tested, 39% GWI + , 18.4% testing-COVID + , 10.6% COVID + hospitalized) suggested GWI + potentially associated with significantly increased COVID-hospitalization risk (adjOR=2.21, 95%CI: 1.02–4.81, p = 0.04); though no significant excess was observed for COVID-related ICU admission or mortality. Conclusions Our findings demonstrated that overall deployment to serve in the 1990–1991 Gulf War was not associated with increased COVID-related health risks among Gulf War era veterans using VA healthcare system in early pre-vaccine pandemic era. Preliminary findings suggesting association between Gulf War Illness and potential increased COVID-related hospitalization risk among deployed Gulf War veterans in the early pandemic era warrants replication and ongoing evaluation to assess if it persists in the era of COVID vaccination, oral anti-COVID medications and new viral variants.